Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.